Ring Opening Polymerization of Organic Carbonates Using CO2 ‐ Carbene Adducts as Effective Organo Catalyst. Issue 1 (December 2013) - Reitz, A.; Wilhelm, R.; Kuckling, D.; Lendlein, Andreas; Neffe, Axel T.
Summary In this study we successfully synthesized Poly(trimethylene carbonate) (PTMC) through carbene‐catalysed ring opening polymerization. The use of CO2‐adducts decreases the air and moisture sensitivity of the carbene and improves the controllability of the reaction. The carbene is freed through dissolving and heating. The reaction can be done in bulk or in solution. Improvements to the system can be made by varying temperature and solvent. We could show that bulk polymerization allows the synthesis of PTMC in a short span of time and good yields.